Comparative study on cost effectiveness and quality characteristics of ghee prepared from different animals milk - Raina, Vickrant; Pathak, Vikas; Goswami, Meena; Singh, Sanjay; Sahu, Vivek (Indian Journal of Dairy Science, 2022)
The present study was conducted to compare the cost effectiveness and physic-chemical properties of ghee prepared from different milch animals. In first experiment, ghee was prepared from Sahiwal, cross breed and Murrah buffalo milk separately from two different methods i.e. traditional method and creamery butter method. Cost of formulation per liter ghee was lowest in Murrah buffalo ghee (MG) per kg was less than Sahiwal ghee (SG) and cross breed ghee (CG) for both methods, again creamery butter method was found cost effective than traditional method for ghee preparation on the basis of raw material and other factors. In next experiment, MG, SG and CG were prepared with butter creamy method and compared for various physico-chemical properties and sensory evaluation. Among the physico-chemical properties, BR, iodine, polenske values and cholesterol content of SG and CG were significantly (P